2013
DOI: 10.1016/j.surg.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a and miR-483-5p are candidate serum biomarkers for adrenocortical tumors

Abstract: Background Nonfunctioning adrenal incidentalomas are common and many patients undergo adrenalectomy to exclude adrenocortical carcinoma (ACC). Recent studies have shown dysregulated microRNA expression in ACC. The objective of this study was to determine the feasibility and diagnostic accuracy of measuring serum microRNAs in patients with benign and malignant adrenocortical tumors. Method Five microRNAs were selected from microRNA profiling studies in ACC (miR-let-7d, -34a, -195, -214, and 483-5p). Total mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 16 publications
4
84
2
2
Order By: Relevance
“…A loss of heterozygosity of this chromosome region has been reported in 84% of adrenocortical carcinomas and 30% of adenomas [29,30]. Accordingly, miR-195 is down-regulated in adrenocortical carcinomas both at the tissue [15,17,19] and serum levels [20]. In our series, low miR-195 was a feature of functioning and β-catenin negative tumors, but no correlation was found with p53 protein expression.…”
Section: Differential Expression Of Mirnas Investigated In Adenoma Vscontrasting
confidence: 38%
See 2 more Smart Citations
“…A loss of heterozygosity of this chromosome region has been reported in 84% of adrenocortical carcinomas and 30% of adenomas [29,30]. Accordingly, miR-195 is down-regulated in adrenocortical carcinomas both at the tissue [15,17,19] and serum levels [20]. In our series, low miR-195 was a feature of functioning and β-catenin negative tumors, but no correlation was found with p53 protein expression.…”
Section: Differential Expression Of Mirnas Investigated In Adenoma Vscontrasting
confidence: 38%
“…In NCI-H295R adrenocortical carcinoma cell line, miR-483-5p promotes cell proliferation, but has no effect on apoptosis [18], while miR-483-3p, targeting the pro-apoptotic protein PUMA [25], protects cells from apoptosis [18]. They were consistently found to be over-expressed in comparison with adenomas [15][16][17][18][19][20] and reciprocally correlated [15]. As expected, we found a strong reciprocal correlation among miR-483-3p and miR-483-5p (r= 0.7380, p=<0.0001).…”
Section: Differential Expression Of Mirnas Investigated In Adenoma Vsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, miR-483-5p has been demonstrated to be overexpressed both in the primary tumor (Soon et al 2009, Patterson et al 2011, Duregon et al 2014b) and the bloodstream (Chabre et al 2013, Patel et al 2013, Szabó et al 2014). Chabre and coworkers showed that high circulating serum levels of miR-483-5p and low circulating levels of miR-195 in 21 ACCs stratified into non-aggressive and aggressive cancers were associated with both shorter DFS and OS (Chabre et al 2013).…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…A mellékvese daganatos állapotaiban felfedezett keringő mikroRNS-ek [29,30]. Kutatócsoportunk is vizsgálta korábban a mellékvesekéreg-carcinoma keringő mikro-RNS-mintázatát.…”
Section: Táblázatunclassified